Rheinheimera mangrovi sp. nov., a bacterium isolated from mangrove sediment. Issue 12 (14th December 2020) - Zhang, Weiyan; Zhu, Suting; Cheng, Yuping; Ding, Lijian; Li, Shengying; Peng, Nan; He, Shan
Abstract : A Gram-stain-negative, rod-shaped, motile and strictly aerobic bacterium, designated LHK132 T, was isolated from a mangrove sediment sample collected in Haikou, Hainan Province, PR China. Strain LHK132 T was able to grow at temperatures of 10–45 °C, at salinities of 0–7.0 % (w/v) and at pH 6.0–9.0. Catalase and oxidase activities, H2 S production, urease and methyl red reaction were positive. Indole, nitrate reduction, hydrolysis of gelatin, starch, casein and Tweens 20, 40, 60 and 80 were negative. The major cellular fatty acids were C16 : 0 and summed feature 3 (C16 : 1 ω 7 c and/or C16 : 1 ω 6 c ). The only respiratory quinone was ubiquinone-8. The major polar lipids were phosphatidylethanolamine and phosphatidylglycerol. According to 16S rRNA gene sequence analysis, strain LHK132 T had 98.3, 97.5, 97.4, 97.2 and 97.1% similarities to Rheinheimera soli BD-d46 T, Rheinheimera sediminis YQF-1 T, Rheinheimera tangshanensis JA3-B52 T, Rheinheimera mesophila IITR-13 T and Rheinheimera arenilitoris J-MS1 T, respectively. Phylogenetic analyses indicated that strain LHK132 T formed a distinct lineage with R. soli BD-d46 T within the genus Rheinheimera . The average nucleotide identity and digital DNA–DNA hybridization values between strain LHK132 T and related species of the genus Rheinheimera were well below the thresholds for species delineation. The DNA G+C content was 46.7 mol%. On the basis of its phenotypic, chemotaxonomic and genotypic data, strain LHK132 T is considered a representative of a novel species in the genus Rheinheimera, for which the name Rheinheimera mangrovi sp. nov. is proposed. The type strain is LHK132 T (=KCTC 62580 T =MCCC 1K03529 T ).